Memora - Lama Ibrahim; Dana Breik (My University, 2025)
Memora is an innovative learning platform which is designed in order to enhance the student’s educational experience through several tools. In the first place, it integrates flashcard-based learning with (SRS) to optimize long-term memory retention by scheduling card reviews based on the user performance. Correct answers extend the review interval, while incorrect answers shorten it to reinforce the learning process. Statistics and charts are used to track the user’s progress. In addition to that, there’s a customizable Pomodoro timer based on the Pomodoro technique, where the user will be segmenting the study sessions into focused intervals followed by short breaks, enhancing productivity and concentration. Users can personalize these sessions, track completed cycles, and link them to specific learning tasks, promoting efficient study habits. A third feature included is a rich text note taking section where the user can store his notes efficiently. The basic roles in this platform are users(learners), educators(instructors), parents and administrator. Learners’ main aim is to focus on their study progress, educators create and monitor content, parents oversee their child’s learning journey and administrators manage the overall system. By combining these features and roles, Memora offers a holistic, collaborative, and interactive learning environment, effectively addressing the diverse needs of users while promoting structured and effective learning.